Sentinel Headache as a Prodrome of Aneurysmal Rupture: a Systematic Review - Ribeiro, Rodrigo Mariano; Vasconcelos, Sophia Costa; Parente, Ana Cecilia Neves Rios; Santos, Ana Luiza Souza; Gomes, Emanuel de Assis Bertulino Martins; Oliveira, Anna Melissa Noronha; Junior, Fernando Antonio Guimaraes; Neto, Pedro Braga (Headache Medicine, 2023)
Full abstract in PDF.